2021
DOI: 10.51329/mehdiophthal1425
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporium apiospermum contact lens-related keratitis: A rare case report and a literature review

Abstract: Background: Scedosporium apiospermum (SA) is commonly present in temperate climates. It can induce cutaneous and subcutaneous tissue infections as well as disseminated infections in immunocompromised or immunocompetent hosts. The eye is rarely involved. Keratomycosis is usually caused by plant-related injuries. Here, we describe a patient with a severe and sight-threatening corneal abscess caused by SA, which was associated with contact lens wear and was successfully treated with a combination of surgical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In previous case reports and literature review, a few cases of ocular infection due to Scedosporium were observed even in immunocompetent patients, resulting in vision loss or evisceration/enucleation despite medical and surgical treatment [ 6 ]. It is also suggested that early diagnosis, along with proper treatment, is the most important determinant of the prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous case reports and literature review, a few cases of ocular infection due to Scedosporium were observed even in immunocompetent patients, resulting in vision loss or evisceration/enucleation despite medical and surgical treatment [ 6 ]. It is also suggested that early diagnosis, along with proper treatment, is the most important determinant of the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Contamination of the cleaning solution may also have caused this condition. As of now, only three cases of keratitis due to S. apiospermum have been reported after wearing contact lenses [ 6 , 8 , 9 ]. The first case was treated with topical voriconazole and intravenous voriconazole [ 6 ], the second case (with endophthalmitis and had pars plana vitrectomy) was treated with intravenous voriconazole and intravitreal voriconazole [ 8 ], and the last case was treated with topical econazole (1%) and amphotericin B (0.15%) with oral itraconazole (200 mg daily) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%